2001
DOI: 10.1002/jcb.1081
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian recombination hot spot in a DNA loop anchorage region: A model for the study of common fragile sites

Abstract: We analyzed the replication pattern and the topological organization of a 200 kb long Chinese hamster polygenic locus, which spans the boundary of two isochores. One of them is G C rich while the second one is highly A T rich. Previous analysis of mutants ampli®ed for this locus had identi®ed, within the A T rich isochore, a mitotic recombination hotspot and a replication origin separated by some 7 kb. The recombination hotspot exhibits structural features repeatedly observed at common fragile sites, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
19
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 50 publications
(74 reference statements)
8
19
0
Order By: Relevance
“…In contrast, the DMPK sequence is 60% G ϩ C-rich, and the (CTG⅐CAG) n repeats are 67% G ϩ C-rich. Several prior studies (52,(72)(73)(74) have suggested that A ϩ T-rich sequences are recombinogenic. Therefore, it is possible that the ϳ60% A ϩ T richness of the phage fragments (contrasted to the ϳ40% A ϩ T content of the DMPK sequence) is at least partly responsible for the higher apparent recombination frequency for the 564-bp fragments.…”
Section: Instability Of the Ctg⅐cag Tracts In The Recombinationmentioning
confidence: 99%
“…In contrast, the DMPK sequence is 60% G ϩ C-rich, and the (CTG⅐CAG) n repeats are 67% G ϩ C-rich. Several prior studies (52,(72)(73)(74) have suggested that A ϩ T-rich sequences are recombinogenic. Therefore, it is possible that the ϳ60% A ϩ T richness of the phage fragments (contrasted to the ϳ40% A ϩ T content of the DMPK sequence) is at least partly responsible for the higher apparent recombination frequency for the 564-bp fragments.…”
Section: Instability Of the Ctg⅐cag Tracts In The Recombinationmentioning
confidence: 99%
“…14,15 OriGNAI3 was also revealed in nonamplified CHO cells with the "leading strand polarity" origin mapping technique. 16 Three-color painting of DNA fibers from three independent mutants repeatedly disclosed initiation events within a region centered on the one previously determined by the other methods (Fig. 2).…”
mentioning
confidence: 60%
“…Indeed, in CHO cells that exhibit a high activity of oriGNAI3, only the MAR containing that origin is attached in vivo to the matrix, as judged by its unique sensitivity to Topo2 inhibitor VM26. 16 Thus, it is tempting to speculate that the attachment of AT-rich sequences to the nuclear skeleton correlates with a high firing efficiency. Whether the alterations of nucleotide pools that modify the replication pattern at this locus also promote remodeling of chromatin loops is currently under investigation.…”
mentioning
confidence: 99%
“…Recombination in mitotic cells is reported for several species, ranging from placental mammals (Cornforth & Eberle, 2001;Svetlova et al, 2001) to insects (Stern, 1936;Bartsch et al, 1997) and yeast (Huang & Keil, 1995). For example, in the yeast Saccharomyces cerevisiae, the recombination hotspot HOT1 initiates mitotic recombination when inserted into novel locations throughout the genome (Huang & Keil, 1995).…”
Section: Discussionmentioning
confidence: 99%